Acetate‐containing substrate mixtures improve recombinant protein secretion in Schizosaccharomyces pombe. Issue 4 (5th March 2015) - Klein, Tobias; Heinzle, Elmar; Schneider, Konstantin
<x xml:space="preserve">Abstract</x> Recombinant protein secretion in yeasts poses a burden to the metabolism of the host cell. Consequently, unfavorable cultivation conditions during strain screening or process development can lead to limitations in the energy and carbon metabolism of the cell, constraining the cell's ability to secrete the protein of interest. Recently, we demonstrated that improving cultivation conditions by using substrate mixtures of glycerol and acetate strongly elevated secretion of the homologous model protein maltase in the fission yeast Schizosaccharomyces pombe. In this work, we investigated if these previous findings were also applicable to the expression of recombinant proteins. Strains were constructed secreting either green fluorescent protein or a fluorescent single‐chain antibody fragment. These strains were cultivated under fermentative and respiratory growth conditions on glucose as sole carbon source and on mixtures of glucose/acetate and glycerol/acetate. We observed an increase in the specific secretion of both recombinant proteins by 1.8‐ and 3.8‐fold, respectively. This clearly demonstrates that the proper choice of process conditions and the applied carbon sources have a significant impact on the secretion of at least two recombinant proteins in S. pombe allowing an improved production of the protein of interest.